The Role of Perceived Social Support on Loneliness in Predicting the Level of Depression in Social Media Users - Rita Octaviane; Roswiyani Roswiyani (Faculty of Psychology, Universitas Semarang, 2024)
Prolonged social media use can increase loneliness and potentially affect mental health, including depression. This study explored the effect of perceived social support on loneliness in predicting depression in 134 early adult social media users (18-34 years old) who used social media more than 3 hours per day and experienced mild depression (PHQ-9). Instruments included the UCLA Loneliness Scale version 3, MSPSS, and BDI-II. Regression analysis with moderation showed that perceived social support did not significantly moderate the relationship between loneliness and depression (p > 0.05). However, social support from family had a significant direct effect in reducing depression (p < 0.05), while the dimensions of friends and significant others were not significant. These results indicate that although perceived social support is not strong enough as a moderator in the loneliness-depression relationship, the family dimension still plays an important role directly in reducing depression. The direct results indicate a direct contribution to depression through the family dimension. Thus, although perceived social support as a whole does not moderate this relationship, certain dimensions still have a direct effect. Keywords: Depression; Early adulthood; Loneliness; Social media; Social support